HRas and Myc synergistically induce cell cycle progression and apoptosis of murine cardiomyocytes - Boikova, Aleksandra; Bywater, Megan J.; Quaife-Ryan, Gregory A.; Straube, Jasmin; Thompson, Lucy; Ascanelli, Camilla; Littlewood, Trevor D.; Evan, Gerard I.; Hudson, James E.; Wilson, Catherine H. (Frontiers in Cardiovascular Medicine, 2022)
Aim Adult mammalian cardiomyocytes are incapable of significant proliferation, limiting regeneration after myocardial injury. Overexpression of the transcription factor Myc has been shown to drive proliferation in the adult mouse heart, but only when combined with Cyclin T1. As constitutive HRas activity has been shown to stabilise Cyclin T1 in vivo, we aimed to establish whether Myc and HRas could also act cooperatively to induce proliferation in adult mammalian cardiomyocytes in vivo. Methods and results Using a genetically modified mouse model, we confirmed that constitutive HRas activity (HRasG12V) increased Cyclin T1 expression. HRasG12V and constitutive Myc expression together co-operate to drive cell-cycle progression of adult mammalian cardiomyocytes. However, stimulation of endogenous cardiac proliferation by the ectopic expression of HRasG12V and Myc also induced cardiomyocyte death, while Myc and Cyclin T1 expression did not. Conclusion Co-expression of Cyclin T1 and Myc may be a therapeutically tractable approach for cardiomyocyte neo-genesis post injury, while cell death induced by HRasG12V and Myc expression likely limits this option as a regenerative therapeutic target.